Effectiveness of recruitment & selection process in Grameen Danone Foods Limited - Mumu, Sadia Amreen (BRAC Univeristy, 2017)
This internship report is submitted in a partial fulfilment of the requirements for the degree of Bachelor of Business Administration, 2017.